Inseminasi Buatan Berbasis Semen Beku Sexing-Sperm Guna Memperbaiki Kinerja Reproduksi Sapi dan Biogas Sebagai Sumber Energi Alternatif di Desa Kuripan Karangawen Demak - Achmad Buchori; Mega Novita; Dian Ayu Azhari (Journal of Dedicators Community, 2021)
Kuripan is a village in Karangawen District, Demak Regency, Central Java Province, Indonesia. Based on the source of statistical data for Kuripan Village, Karangawen District, Demak Regency in 2019, people who are in the lower economy are quite high, at about 40%. Basically Kuripan Village has good potential in the livestock sector. The majority of Kuripan Village residents raise beef cattle which fill the Central Java market, around 214,830 Kg per year. Even so, they have not been able to optimize their potential to improve the welfare of their citizens. Through a program of dissemination of appropriate technology products, artificial insemination based on sexing-sperm frozen semen and a digester that produces biogas and organic fertilizers were applied in Kuripan Village. The community development method used in this work makes the community both as the subject and as the object. The result of this activity is an increase in the knowledge and motivation of the residents which ultimately increases their income